The effect of extremely weak pulsed electromagnetic field treatments upon signs and symptoms of delayed onset of muscle soreness; a placebo controlled clinical double blind study - Spodaryk, K. (Medicina Sportiva, 2002)
The effect of pulsed weak electromagnetic fields upon experimentally induced delayed onset of muscle soreness (DOMS) was assessed in a placebo controlled clinical double blind study. DOMS was induced in 36 volunteers and the elbow flexors of the non-dominant arm were used for a standardized eccentric exercise regime. Subjects were randomly allocated to one of the three groups: control (C, n=12), sham-treated (S-T, n=12) and treated with a special kind of pulsed electromagnetic fields (T, n=12) by applying the BEMER 3000 local therapy intensive applicator. Volunteers from group T were electromagnetically stimulated each day with a magnetic field of 86 ?T. Subjects from the sham-treated group were treated by deactivated BEMER 3000 systems. One-way analysis of variance (ANOVA) demonstrated significant effects of electromagnetic field treatment on retarding pain intensity as measured by visual analogue scale (VAS) (p<0.05). According to standard methods of goniometrical measurements statistically significant differences in the range of movement between the control-, sham-treated- and electromagnetic treated groups were further found on the second day of the experiments. Within the conditions of the current experiments the pulsed electromagnetic (BEMER 3000) field treatment exerts clearcut and favourable effects upon the cardinal signs and symptoms of DOMS.